Optimize Backwashing and Filter Ripening Processes. Issue 3 (5th March 2019) - Martin, Barb; Linder, Kevin
Abstract : As part of best practices for achieving peak water treatment performance, filtration operation and maintenance are critical. Optimize your facility's backwashing and filter ripening processes for best results.